Evolución del pensamiento cubano sobre Cuba y la economía mundial a través de las revistas económicas - Roca, Sergio G. (Estudios Internacionales, 1993)
This paper explores the evolution of Cuban revolutionary thought about Cuba and the international economy prior to the socialist collapse through its development in the island's economic magazines. The information sources (magazines) that make up the research database are presented and evaluated, as well as a discussion of various factors influencing the quality and usefulness of the information (policy, availability). Then an analysis and assessment of Cuban economic thinking is carried out on six topics: economic integration, unequal exchange, foreign debt, bilateral relations with the Soviet Union, prices and exchange rates, and diversification/industrialization.